Recurrent congenital diaphragmatic hernia associated with intestinal malrotation - Romero Garza, Héctor H.; Morales Gonzalez, Patsy A.; Oviedo Aguilar, Patricia E.; Saldívar Martínez, Daniel; Vázquez Fernández, Francisco; Muñoz Maldonado, Gerardo E. (Revista Argentina de Cirugía, 2021)
Recurrence of congenital diaphragmatic hernia, after surgical repair, is infrequent. Here, we report the case of a 22-year-old male patient with a history of congenital diaphragmatic disease initally treated with surgery on the second day of life who presented class I dyspnea and gastroesophageal reflux. A left diaphragmatic hernia with a hernia sac containing the spleen, colon, tail of pancreas and left adrenal gland. The patient underwent surgical repair via a left subcostal incision; the hernia sac was reduced, the diaphragmatic defect was repaired with a mesh and the Ladd procedure was performed due to the diagnosis of intestinal malrotation.